A Study on Multipath Routing Security Protocols for Mobile Ad Hoc Networks - Reddy, Y Vasudeva; Nagendra, M (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad hoc network (MANET) is a multi-hop wireless network that requires no infrastructure. The major issue in developing the routing protocols for the MANETs is their dynamic topology. The traditional single path routing protocols are not efficient for secure communication. Multipath routing protocols provide higher throughput and security than uni-path routing protocols in MANETs. The objective of the paper is to study various security attacks relevant to multipath routing in MANET which helps in developing a reliable, secure multipath routing protocol with significant performance in MANETs.